Printed liquid crystal optical vortex beam generators - Li, M; Elston, S; He, C; Qiu, X; Castrejón-Pita, A; Morris, S (Wiley, 2024)
This study presents an innovative application of inkjet printing technology in the construction of a switchable optical vortex beam generator. The fabrication process involves drop-ondemand printing of liquid crystal (LC) droplets, which can generate an optical vortex beam in the far-field with the application of a voltage. Notably, this vortex beam can be activated and deactivated by manipulating the amplitude of the electric field. Both simulations and experiments are used to determine the optical characteristics of the printed LC devices and the resulting far-field patterns for different polarizations of light. The study showcases the versatility of the generator in that it can produce both vortex beams and vector fields, the choice of which is simply determined by the polarization of the input light. This highlights the potential of this printed LC technology for integration into a multitude of optical systems.